Ordered Mesoporous Metal–Phenolic Network Particles - Lin, Zhixing; Zhou, Jiajing; Cortez-Jugo, Christina; Han, Yiyuan; Ma, Yutian; Pan, Shuaijun; Hanssen, Eric; Richardson, Joseph J; Caruso, Frank (Journal of the American Chemical Society, 2020)
Mesoporous metal–organic networks have attracted widespread interest owing to their potential applications in diverse fields including gas storage, separations, catalysis, and drug delivery. Despite recent advances, the synthesis of metal–organic networks with large and ordered mesochannels (>20 nm), which are important for loading, separating, and releasing macromolecules, remains a challenge. Herein, we report a templating strategy using sacrificial double cubic network polymer cubosomes (Im3̅m) to synthesize ordered mesoporous metal–phenolic particles (meso-MPN particles) with a large-pore (∼40 nm) single cubic network (Pm3̅m). We demonstrate that the large-pore network and the phenolic groups in the meso-MPN particles enable high loadings of various proteins (e.g., horseradish peroxidase (HRP), bovine hemoglobin, immunoglobulin G, and glucose oxidase (GOx)), which have different shapes, charges, and sizes (i.e., molecular weights spanning 44–160 kDa). For example, GOx loading in the meso-MPN particles was 362 mg g–1, which is ∼6-fold higher than the amount loaded in commercially available SiO2 particles with an average pore size of 50 nm. Furthermore, we show that HRP, when loaded in the meso-MPN particles (486 mg g–1), retained ∼82% activity of free HRP in solution and can be recycled at least five times with a minimal (∼13%) decrease in HRP activity, which exceeds HRP performance in 50 nm pore SiO2 particles (∼36% retained activity and ∼30% activity loss when recycled five times). Considering the wide selection of naturally abundant polyphenols (>8000 species) and metal ions available, the present cubosome-enabled strategy is expected to provide new avenues for designing a range of meso-MPN particles for various applications.